2020
DOI: 10.3390/jcm10010003
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of Diabetic Retinopathy Is an Independent Factor for the Progression of Diabetic Nephropathy

Abstract: (1) Background: It has rarely been studied whether the severity of diabetic retinopathy (DR) could influence renal disease progression in end-stage renal disease (ESRD) and chronic kidney disease (CKD) in patients with type 2 diabetes. The aim of this study was to evaluate renal disease progression in ESRD and CKD according to DR severity in patients with type 2 diabetes. (2) Methods: We included 1329 patients and divided the cohort into two end-points. The first was to trace the incidence of ESRD in all enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…It has also been found that DN is an independent risk factor for the development and progression of DR ( Butt et al, 2020 ). Finally, the severity of DR is a risk factor for progression to CKD in patients with type 2 diabetes ( Hsing et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that DN is an independent risk factor for the development and progression of DR ( Butt et al, 2020 ). Finally, the severity of DR is a risk factor for progression to CKD in patients with type 2 diabetes ( Hsing et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the numerous fundus color photography results, it was not possible to record them one by one. Therefore, we used a software we have developed previously to grade DR [ 16 ]. The deep learning model was based on the convolutional neural network.…”
Section: Methodsmentioning
confidence: 99%
“…Because it is not possible for experts to review large numbers of fundus color photography tests one by one, we used a DLM that we developed previously to grade DR [ 10 ]. The model architecture was based on a 50 layer SE-ResNeXt [ 11 ].…”
Section: Methodsmentioning
confidence: 99%